Un panaméricanisme à la brésilienne ? Le projet d’Institut Interaméricain de Coopération Intellectuelle (1926-1930) - Juliette Dumont (Centre de Recherches sur les Mondes Américains, 2016)
This paper is an extract of the sixth chapter of my doctoral thesis entitled ‘From Intellectual Cooperation to Cultural Diplomacy: the Argentinian, Brazilian and Chilean Experiences (1919-1946)’ where I examine how Argentina, Brazil and Chile developed their cultural diplomacy by using networks and practices stemming from international cooperation during the interwar period. This paper adopts a multi-scalar approach: I will first explore the international role played by the predecessor of the UNESCO, the International Institute of Intellectual Cooperation created by the League of Nations in 1926. Secondly, I will assess the regional role played by the Pan-American Union which dealt with cultural exchanges between different states throughout the continent. The Latin-American countries perceived the International Institute of Intellectual Cooperation and the Pan-American Union as two potential alternatives to counterbalance the power of Europe on the one hand and the United States on the other hand. The participation of Argentina, Brazil and Chile in both international and regional institutions also constitutes a manner in which these countries constructed their image on the international scene in order not to appear as simple peripheries. This paper will especially focus on Brazil’s project of an Inter-American Institute of Intellectual Cooperation and will shed light on the way the country tried to position itself on the continent. The Brazilian initiative is also a perfect case-study to understand the debates surrounding intellectual cooperation.